Emulsifiers modulate the extent of gastric lipolysis during the dynamic in vitro digestion of submicron chia oil/water emulsions with limited impact on the final extent of intestinal lipolysis. (March 2022) - Pizones Ruiz-Henestrosa, Víctor M.; Ribourg, Lucie; Kermarrec, Alice; Anton, Marc; Pilosof, Ana; Viau, Michelle; Meynier, Anne
Abstract: Consumer demands for healthier foods are constantly on the rise and results in the diversification of sources such as vegetable oils. Chia oil is a relevant source of α-linolenic acid. One of the targeted applications is the inclusion of chia oil in emulsified form in beverages where it is necessary to obtain stable submicron emulsions, acting as carrier of nutrients such as lipids. In the present work, high-pressure homogenization was employed to produce emulsions (10% chia oil) with small oil droplets (300 nm), formulated with different emulsifiers (beta-lactoglobulin (BLG), lecithin and Tween 80). These emulsions were submitted to a dynamic in vitro digestion (DIDGI) to better understand the main mechanisms involved in the process of lipolysis, in order to design systems that may allow the modulation of the digestive action of lipases, thus ensuring the maximum bioaccessibility of the lipids. This device mimics part of the transient biochemical conditions as well as the flow of foods through the different compartments occurring in the real digestion. Significant differences were observed in the lipolysis during the gastric phase. BLGemulsions reached a lipolysis degree of 30%. Lecithin-stabilized emulsions behave similarly to BLG ones during the first 90 min but lipolysis levelled off further ∼20%. Finally, Tween-80-stabilized emulsions remained almost undigested (around 2%). No significant differences were noticed in duodenum and distal small intestine, irrespective of the emulsifier employed. After digestion, the fatty acid bioaccessibility was higher with BLG as emulsifier. Graphical abstract: Image 1 Highlights: Chia O/W emulsions (similar droplet size) were produced with BLG, LEC and T80. Lipolysis and bioaccesibility was evaluated with an in vitro dynamic device (DIDGi). T80 emulsions exhibited the lowest extent gastric lipolysis. Bioaccessibility of fatty acids were slighltly higher for BLG emulsion.